Partisipasi Masyarakat terhadap Penerapan Instalasi Pengolahan Air Limbah Sistem Komunal untuk Kebersihan Lingkungan Kelurahan Lakkang Kota Makassar - Mithen Lullulangi (Seminar Nasional LP2M UNM, 2017)
This study aims to determine the level of community participation and public perception of environmental hygiene after the application of the Waste Water Treatment Plant (WWTP) in the Village Communal Lakkang Makassar. This research uses descriptive quantitative method. Samples numbered 40 heads of households using saturation sampling technique. Data collected by observation, documentation and questionnaires. Data analysis using descriptive statistics. The results showed: (1) Public participation in the implementation of the WWTP Communal Village Lakkang Makassar City is at a level high participation where the planning stage form of community participation is realized in the form of donations of ideas or opinions and at the implementation stage of development, utilization, and maintenance is realized in the form labor, material and other forms of contributions, (2) public perception of environmental cleanliness in the Village Lakkang after the implementation of the Communal WWTP show a positive condition.